Price Volatility of Hogs and Tracing of the Event in China: Based on CEEMDAN Method - Lv, Xi; Tu, Guoping; Li, Heng (Frontiers in Energy Research, 2022)
Since May 2018, the price of this hog cycle has increased by 196%, and the absolute price and its volatility are far beyond history. The violent fluctuation of hog prices seriously affects the sustainable development of the hog industry. This work uses the monthly data of hog prices from January 2010 to July 2021 to carry out an empirical analysis to examine the characteristics of the fluctuations and its influencing factors and employs CEEMADN to perform multi-scale feature decomposition on the price of hogs in China. Then, this study adopts the fine-to-coarse recombination algorithm to reconstruct components. Finally, the Bai–Perron structural breakpoint test is performed on the reconstructed components to find the basis for important events that affect the price fluctuation of hogs. Results show that the low-frequency components representing important regulatory policies and the trend components representing long-term development trends play a major role in the price trend of hogs. There are four structural breakpoints in the low-frequency components, indicating that the country’s regulatory policies for African swine fever, land and environmental problems, and tight supply and demand can effectively increase the hog production capacity and stabilize the hog market.